Ethnic Identity, Self-esteem, and Academic Performance of Nigerian In-school Adolescents - Adams Ogirima Onivehu (Charles University, 2022)
The development of ethnic identification plays an integral role in the formation of the self among in-school adolescents, especially in Nigeria, which is largely a multicultural and multi-ethnic nation. Thus, the present study investigated the extent to which ethnic identity and self-esteem could predict academic performance among Nigerian in-school adolescents. Methods: A total of 735 Nigerian in-school adolescents in public and private senior secondary schools in Ilorin, Kwara State, Nigeria participated in the study. The independent variables (ethnic identity and self-esteem) were assessed using the Multi-Ethnic Identity Measure (MEIM) and the Rosenberg Self-esteem Scale (RSE) respectively. The data was subjected to frequency counts, percentage analysis, correlation analysis, and multiple regression. Results: The results of this study showed that a majority of the respondents were identified as having a high level of ethnic identity and self-esteem. Furthermore, ethnic identity and self-esteem were significant predictors of academic performance. Recommendations: Hence, it was recommended that the development of the self-identity and group-identity of Nigerian in-school adolescents should be facilitated through various psychosocial interventions.